Desain dan Uji Validitas e-Modul Perkuliahan Kimia Fisika Berbasis Problem Based Learning - Mutiara Dwi Cahyani; Tania Avianda Gusman (Orbital: Jurnal Pendidikan Kimia, 2023)
The rapid development of technology requires education to participate in the use of technology as an innovation in learning. The purpose of this research is to develop and test a surface tension e-module based on Problem Based Learning in the Chemistry Physics course. The research method used in this study is Research and Design using the ADDIE development model which is limited to the analysis, design and development stages. The instrument used to determine the feasibility of the e-module is a questionnaire to test the validity of media experts and material experts. Respondents for testing the validity of media experts and material experts were educators in university and high schools. The feasibility level of the e-module is based on the validation of material experts by 80% which states that the quality of the material in the e-module is feasible from the material aspect and is based on problem based learning, the validation of media experts is 86.7% which states that the quality of the display on the e-module is very decent from the aspect of the media. This shows that the surface tension e-module based on problem based learning is feasible to use and implement in the learning process for university and high school levels.